2010
DOI: 10.1111/j.1600-079x.2010.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates methamphetamine‐induced overexpression of pro‐inflammatory cytokines in microglial cell lines

Abstract: Methamphetamine (METH), the most commonly abused drug, has long been known to induce neurotoxicity. METH causes oxidative stress and inflammation, as well as the overproduction of both reactive oxygen species (ROS) and reactive nitrogen species (RNS). The role of METH-induced brain inflammation remains unclear. Imbroglio activation contributes to the neuronal damage that accompanies injury, disease and inflammation. METH may activate microglia to produce neuroinflammatory molecules. In highly aggressively prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 49 publications
4
68
0
Order By: Relevance
“…Melatonin at 1 nM, which approximates the physiological concentration of the pineal hormone at night, significantly inhibited TNF-a, IL-1b, IL-6, and iNOS overexpression induced by methamphetamine (METH) in microglia (184). In addition, the antiinflammatory effect of melatonin against these METHinduced neuroinflammatory events also occurs in human neuroblastoma dopaminergic cells (185).…”
mentioning
confidence: 82%
“…Melatonin at 1 nM, which approximates the physiological concentration of the pineal hormone at night, significantly inhibited TNF-a, IL-1b, IL-6, and iNOS overexpression induced by methamphetamine (METH) in microglia (184). In addition, the antiinflammatory effect of melatonin against these METHinduced neuroinflammatory events also occurs in human neuroblastoma dopaminergic cells (185).…”
mentioning
confidence: 82%
“…Recent studies have demonstrated that METH is a neurotoxic drug that can induce neuronal (Ajjimaporn et al, 2005;Zhu et al, 2006;Deng et al, 2007) and glial cell death by several pathways, including oxidative stress (Riddle et al, 2006;Tocharus et al, 2008), mitochondrial dysfunction (Brown et al, 2005;Jumnongprakhon et al, 2014), excitotoxicity (Staszewski and Yamamoto, 2006;Ernst and Chang, 2008), inflammatory responses (Jumnongprakhon et al, 2015), and ER stress (Shah and Kumar, 2016). We have previously reported that exposure to METH causes an overproduction of ROS (Tocharus et al, 2010) that leads to oxidative stress. METH also induces cell death mediated by the apoptosis pathway through the mitochondrial death pathway (Imam et al, 2001;Thiriet et al, 2001;Jumnongprakhon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological functions of melatonin include circadian maintenance, sleep promotion, and immune enhancement (Nelson and Drazen, 2000;Zisapel, 2001;Pandi-Perumal et al, 2008;Tan et al, 2009;Manchester et al, 2015). Our previous studies suggested that melatonin is a neuroprotective agent that can down-regulate the expression of not only reactive oxygen species (ROS) and nitric oxide (NO) but also pro-inflammatory cytokines (Tocharus et al, 2008(Tocharus et al, , 2010. Moreover, melatonin also attenuates METH-induced glial cell death by decreasing the inflammatory responses and the mitochondrial death pathway (Jumnongprakhon et al, 2014(Jumnongprakhon et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of METH induces toxicity in both neuronal and glial cells, mediated by an increase in reactive oxygen species (ROS) [3][4][5][6] and pro-inflammatory cytokines such as tumor necrosis factor-a (TNF-a), interleukin (IL)-6, IL1b, and nitric oxide (NO) both in vitro [7][8][9][10] and in vivo [11][12][13] that play important roles in the pathogenesis of neurodegenerative diseases such as Parkinson's disease and Alzheimer's disease [14][15][16][17]. Recently, it has become widely accepted that the response of the microglial cells or astrocyte cells to METH is associated with the pathogenesis of diseases [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%